A Framework for Social Science in Epidemics. Issue 1 (1st March 2022) - Ripoll, Santiago; Wilkinson, Annie; Abbas, Syed; MacGregor, Hayley; Hrynick, Tabitha; Schmidt-Sane, Megan
Abstract: In epidemic preparedness and response, it is now commonly accepted that insights from social science disciplines are important in shaping action. Unfortunately, the role of social science is often confined to risk communication and community engagement (RCCE) efforts. In this article, we propose an analytical framework that would allow researchers and practitioners from different disciplines to employ social science insights to enrich their understanding of epidemics and formulate more effective and sustainable responses. The framework goes beyond simply unpacking social, political, economic and cultural dimensions of context; it situates disease itself – as it is shaped by the contexts in which it circulates – and views it in dynamic relation to response. It also explores how different individuals, social groups and institutions shift their knowledge and practices during an epidemic through power-laden processes of dialogue and learning, or even through silencing and side-lining. It is our hope that this framework will enable responders to engage more deeply and systematically with the contexts of emergencies, so as to ensure activities are more adaptive to local dynamics.